2015
DOI: 10.1158/1078-0432.ccr-14-2072
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Self-Renewal and Increased Colitis and Dysplastic Lesions in Colonic Mucosa of AKR1B8-Deficient Mice

Abstract: Purpose Ulcerative colitis (UC) and colitis-associated colorectal cancer (CAC) is a serious health issue, but etiopathological factors remain unclear. Aldo-keto reductase 1B10 (AKR1B10) is specifically expressed in the colonic epithelium, but down-regulated in colorectal cancer. This study was aimed to investigate the etiopathogenic role of AKR1B10 in UC and CAC. Experimental design UC and CAC biopsies (paraffin-embedded sections) and frozen tissues were collected to examine AKR1B10 expression. Aldo-keto red… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 50 publications
1
52
0
Order By: Relevance
“…Very recently, we found that AKR1B10 stimulates metastasis of breast cancer through integrin α5/δ‐catenin mediated FAK/Src/Rac1 signaling pathway . In normal tissues, AKR1B10 is primarily expressed in the colon and small intestine, where it regulates proliferation and self‐renewal of cryptic epithelial cells …”
Section: Introductionmentioning
confidence: 99%
“…Very recently, we found that AKR1B10 stimulates metastasis of breast cancer through integrin α5/δ‐catenin mediated FAK/Src/Rac1 signaling pathway . In normal tissues, AKR1B10 is primarily expressed in the colon and small intestine, where it regulates proliferation and self‐renewal of cryptic epithelial cells …”
Section: Introductionmentioning
confidence: 99%
“…In normal tissues, AKR1B10 is primarily expressed in the colon and small intestine and promotes epithelial cell proliferation regulating epithelial cell self-renewal [16, 24]. Targeted disruption of AKR1B8 (an ortholog of AKR1B10 in mouse) leads to diminished proliferation and migration of epithelial cells and increased susceptibility to carbonyl and oxidative stress-induced DNA damage and tumorigenesis [25]. In tumors, AKR1B10 is upregulated in breast, liver and lung cancers, promoting tumor growth and progression [2629].…”
Section: Introductionmentioning
confidence: 99%
“…AKR1B10 is a secretory protein up‐regulated in HCC . AKR1B10 can eliminate cytotoxic and carcinogenic α and β‐unsaturated carbonyl compounds and regulate de novo fatty acid/lipid synthesis . In normal tissues, AKR1B10 is specifically expressed in the colon and small intestine, where it is secreted into the lumen .…”
mentioning
confidence: 99%